PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT ONOLALU KABUPATEN NIAS SELATAN - Menyesuaikan Zamili (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The background of this research is the leadership style and performance of employees. The purpose of this study was to determine the influence of leadership style on employee performance at the Onolalu Sub-district Office, South Nias Regency. Data collection techniques are research instruments or questionnaires. The data analysis method used is simple linear regression analysis Y=11.849+0.733X. The results of this study showed that the thiitung value of 6,216 >ttabel was 1,549, so the researcher concluded that this study had an influence on leadership style on employee performance at the Onolalu Sub-district Office, South Nias Regency. The suggestion of this research is This research suggestion is (1) To carry out a good job in the Sub-district Office, preferably in the division of labor towards employees is very necessary to be adjusted to the profession and class. (2) In improving employee performance, as an organizational leader, it is necessary to create a work environment to maintain harmony in communication between colleagues.